Knowledge-Based and Intelligent Information and Engineering Systems 14th International Conference, KES 2010, Cardiff, UK, September 8-10, 2010, Proceedings, Part IV - Setchi, Rossitza; Jordanov, Ivan.; Howlett, Robert J.; Jain, Lakhmi C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The four-volume set LNAI 6276--6279 constitutes the refereed proceedings of the 14th International Conference on Knowledge-Based Intelligent Information and Engineering Systems, KES 2010, held in Cardiff, UK, in September 2010. The 272 revised papers presented were carefully reviewed and selected from 360 submissions. They present the results of high-quality research on a broad range of intelligent systems topics.
Knowledge Based and Expert Systems -- Emotion Judgment Method from an Utterance Sentence -- Local Model Update with an Application to Sliding Window Protocol -- Development of RP3CA-EMP, a Knowledge-Based System for Applying Environmental Management Plan (EMP) in the Malaysian Construction Industry -- Reasoning with Multiple Points of View: A Case Study -- Syntax and Semantics for Business Rules -- Dialect Recognition Method Using Emotion Judgment -- Applying a Knowledge Based System for Metadata Integration for Data Warehouses -- A Ubiquitous Intelligent Tutoring System for Aiding Electronic Learning -- Towards a Proposal for a Vessel Knowledge Representation Model -- Developing a Probabilistic Graphical Structure from a Model of Mental-Health Clinical Risk Expertise -- Controlling Security of Software Development with Multi-agent System -- On ?ukasiewicz$1 (BInfinie-Valued Logic and Fuzzy L -- A Meta-level Approach to Approximate Probability -- Comparing Ontologies Using Multi-agent System and Knowledge Base -- ACTL Local Model Update with Constraints -- Knowledge Environment for Supporting Creative Learning -- Bridging Multiple Motor-Skills in a Community Site -- Topic Visualization for Understanding Research Paper in Collaborative Discussion -- Building a Framework to Design and Evaluate Meta-learning Support Systems -- Promoting Learning Attention with Gaze Tracking Integrated e-Learning Contents -- System for Creative Distance Learning Environment Development Based on Competence Management -- A Blended Project-Based Learning Program on Embedded Software Design with Collaboration Support Tools -- Multilingual Discussion in Metaverse among Students from the USA, Korea and Japan -- Improvement of an Annotation Sharing System on Web-Based Materials to Activate Discussions -- Information Communication Technology in Innovation and Creativity -- Where to Crawl Next for Focused Crawlers -- Extraction of Co-existent Sentences for Explaining Figures toward Effective Support for Scientific Papers Reading -- Semantic Approach to Image Retrieval Using Statistical Models Based on a Lexical Ontology -- IEC-Based Motion Retrieval System Using Laban Movement Analysis -- Automatic Composition of Personalized Appreciation Route Based on Semantic Relationship between Exhibits in Museum -- Intelligent Support for Designing Social Information Infrastructure -- Design and Implementation of a Context-Aware Guide Application for Mobile Users Based on Machine Learning -- Adaptive Traffic Signal Control Based on Vehicle Route Sharing by Wireless Communication -- A System to Share Arrangements for Daily Tasks and Life Events on the Web -- Population Estimation of Internet Forum Community by Posted Article Distribution -- Development of Delay Estimation Method Using Probe Data for Adaptive Signal Control Algorithm -- Intelligent Systems in Ambient Assisted Living Environments -- OVACARE: A Multi-Agent System for Assistance and Health Care -- Talking Agents in Ambient-Assisted Living -- A System for Recognizing Activities of Daily Living Using Everyday Objects -- A Normality Analysis-Based Approach to Monitor Behaviors in AAL Domains -- Adaptation of an Evaluation System for e-Health Environments -- OutCare: Supporting Dementia Patients in Outdoor Scenarios -- 3D Visualisation of Natural Language -- Frame Semantics in Text-to-Scene Generation -- SenticSpace: Visualizing Opinions and Sentiments in a Multi-dimensional Vector Space -- Supporting Collaborative Transcription of Recorded Speech with a 3D Game Interface -- Text-to-Video: Story Illustration from Online Photo Collections -- Improving Communication Using 3D Animation -- Visualization and Language Processing for Supporting Analysis across the Biomedical Literature -- SceneMaker: Multimodal Visualisation of Natural Language Film Scripts -- Knowledge-Based Creativity Support Systems -- Interaction Technique Combining Gripping and Pen Pressures -- Destination Board System Based on Photographs -- Practicing on Stage: Increasing Transparency and Interaction in Class Activity with Digital Pen system -- Extracting a Keyword Network of Flood Disaster Measures -- Study on Classification of the Tacit Knowledge Using an Eye-Tracking Interface: Experiment of Observation Pictures and Assessment of Reproduction Drawing -- Tools and Techniques for Effective Creation and Exploitation of Biodiversity Knowledge -- Evolution of the Catalogue of Life Architecture -- A Consensus Method for Checklist Integration -- Tools for Semantic Annotation of Taxonomic Descriptions -- Automated Pre-processing Strategies for Species Occurrence Data Used in Biodiversity Modelling -- Real World Data Mining and Digital Intelligence -- A Hybrid Approach for Indexing and Retrieval of Archaeological Textual Information -- Prognosis of Breast Cancer Using Genetic Programming -- Classification of Software Artifacts Based on Structural Information -- Clustering Client Honeypot Data to Support Malware Analysis -- LocPriS: A Security and Privacy Preserving Location Based Services Development Framework -- Controlling Real World Pervasive Environments with Knowledge Bases -- Automatically Finding Answers to "Why" and "How to" Questions for Arabic Language -- From Information to Sense-Making: Fetching and Querying Semantic Repositories -- Advanced Design Techniques for Adaptive Systems -- A Variable Topology Analog Filter Suitable for Multi-mode Wireless Applications -- A Reconfigurable Voltage Reference without Resistors -- A Double-Layer Genetic Algorithm for Gm-C Filter Design -- Optimised Dielectric Totally Internally Reflecting Concentrator for the Solar Photonic Optoelectronic Transformer System: Maximum Concentration Method.s
Keywords: Computer science; Computer Communication Networks; Database management; Information storage and retrieval systems; Information systems; Artificial intelligence; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Computer Communication Networks; Information Storage and Retrieval; Pattern Recognition; Database Management